A review on the role of activity-based costing information and costs structure integration in supply chain and operations. (1st January 2011) - Khataie, Amir H.; Bulgak, Akif A.
In recent times, activity-based costing (ABC) has been evolving to a managerial and cost accounting system rather than a mere cost accounting. The popularity of integration of the ABC in the mathematical models of supply chain management (SCM) for decision support further emphasises the managerial scope of ABC. In this paper, we review the significant role of ABC information and cost structure integration in supply chain mathematical decision support modelling, with the aim of comparing its applicability at different managerial hierarchy levels. The presented literature provides a framework for evaluating the suitability of ABC into different SCM decision making processes.